Sulphur Doped Graphitic Carbon Nitride as a Dual Biosensing Platform for the Detection of Cancer Biomarker CA15–3. Issue 1 (22nd January 2021) - Sakthivel, Arunkumar; Chandrasekaran, Anitha; Sadasivam, Mohanraj; Manickam, Pandiaraj; Alwarappan, Subbiah
Abstract : Herein, we report a dual biosensing platform operating viz., electrochemical and fluorescence mode for the cancer biomarker, CA15–3 detection. A one-step strategy was employed to synthesize sulphur doped graphitic carbon nitride nanosheets (S-g-C3 N4 ). The presence of heteroatom (sulphur) in the molecular structure improved the optoelectronic properties and the surface functional group (–NH2 ) facilitated the covalent binding of antibodies and improved the selectivity during the analysis. The proposed biosensing platform was able to quantify very low concentration of the cancer biomarker, CA15–3 (2.9 U mL −1 ) in human serum samples and thereby evidenced the usefulness of this platform for clinical analysis and early disease diagnosis.